Older adult supportive environment at home—a case study in Jordan: overall sense of control associated with home modification - Al-Homoud, Majd (Frontiers in Public Health, 2024)
IntroductionModification becomes a critical issue in a supportive home environment for older adults.MethodsThis study examined if modifications in different spaces at home are facilitated to provide a supportive environment for older adults to feel in control in a cultural context. Data was utilized using field research with a mixed method design: Structured and open-ended interviews as well as surveys using a questionnaire. The hypothesis states that older adults have a supportive environment at home when the overall sense of control is associated with home modification.ResultsThe result reveals that overall sense of control with home modification and its components: kitchen, bedroom, living room, and reception room have a significant effect on older adults’ wellbeing.DiscussionTherefore, older adult supported environment in Jordan can only take place by boosting awareness about the existing problems in the physical environment, by describing the benefits of home modification and by reducing the barriers of home modifications. This process can enhance the housing market and provide better urban policies for urban design and urban planning based on cultural heritage and values.